Exploring the Personal Data Protection Methods through Programs - Mahmudova, Shafagat Jabrayil (Discoveries in Agriculture and Food Sciences, 2020)
The paper highlights the personal data and the stages of its protection. Some provisions of the Law of the Republic of Azerbaijan on the personal data are reviewed. The protection of personal data through programs is explored. The studies in this area are reviewed. Data protection methods through programs are studied and analyzed. Some recommendations for the further developments in this field are provided.